THE COURSE OF COVID-19 INFECTION IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The purpose of the study — to study the features of the clinical course of COVID-19 in the presence of diabetes mellitus (DM), as well as possible causes of their mutual aggravation. Materials and methods. The study included 64 patients with COVID-19, including 32 with diabetes (the main group) and 32 without diabetes (the control group). During the hospitalization, the dynamics of clinical, glycemic, coagulation parameters, markers of systemic inflammation, kidney and liver dysfunction were monitored and compared. Results. Viral pneumonia was more severe among patients with DM, as indicated by an increase in the proportion of people with extensive (>50%) lung damage (2.2 times, p=0.05), an increased likelihood of death, and a longer duration of oxygen saturation disorders (p=0.0004). When COVID-19 and diabetes are combined, hyperglycemia is stable, with no pronounced variability, C-reactive protein (p=0.028), creatinine (p=0.035) and fibrinogen (p=0.013) increase to a greater extent and manifestations of hypercoagulation persist longer, including slower normalization of antithrombin III (p=0.012), fibrinogen (p=0.037) and D-dimer (p=0.035). Conclusion. The presence of concomitant diabetes in COVID-19 is associated with a greater severity and prevalence of pneumonia, a persistent decrease in oxygen supply, high hyperglycemia, acceleration of renal dysfunction, systemic inflammatory disorders and hypercoagulation.